The analogy of statute and the analogy of law as doctrinal instruments for legal response to economic challenges - Дришлюк, Володимир Ігорович; Дришлюк, В. І.; Dryshliuk, Volodymyr I.; Чанишева, Аліна Рашидівна; Чанишева, А. Р.; Chanysheva, Alina R.; Бориченко, Катерина Валеріївна; Бориченко, К. В.; Borychenko, Kateryna V.; Кравченко, Сергій Петрович; Кравченко, С. П.; Kravchenko, Serhii P.; et al. (Naguanagua : Universidad de Carabobo, 2025)
Given the growing role of international human rights institutions in the process of harmonizing national legal order with generally recognized human rights standards, there is an objective need to rethink approaches to legal education. The purpose of the study is to clarify the role of the practice of the European Court of Human Rights as a conceptual and applied element in the system of legal education, its influence on the formation of judicial culture and the development of professional legal awareness of future lawyers. The research methodology consists of the following methods: dialectical, formal-logical, comparative-legal and structural-functional methods. The impact of the Court's decisions on the formation of a lawyer's professional identity was considered, in particular in the area of the formation of his law-enforcement culture, worldview orientation on respect for human rights and freedoms, the principle of the rule of law and the principles of independent and impartial judiciary. The need for systematic integration of the Court's case law into the curricula of higher legal education institutions was substantiated, which will contribute not only to the formation of deep theoretical knowledge, but also the ability to properly apply them in practice. Practice-oriented approaches to teaching international human rights standards as a tool for forming a judicial culture that meets the requirements of a legal state are analyzed.
Dryshliuk V. The analogy of statute and the analogy of law as doctrinal instruments for legal response to economic challenges / V. Dryshliuk, A. Chanysheva, K. Borychenko et al. // Eduweb-Revista de Tecnologia de Informacion y Comunicacion en Educacion. – Naguanagua : Universidad de Carabobo, 2025. - Vol. 19(2). - Р. 107-121. URL: https://doi.org/10.46502/issn.1856-7576/2025.19.02.8
Keywords: European Court of Human Rights; legal education; judicial culture; protection of human rights; rule of law